2011
DOI: 10.1128/aem.05352-11
|View full text |Cite
|
Sign up to set email alerts
|

β-Lactams and Florfenicol Antibiotics Remain Bioactive in Soils while Ciprofloxacin, Neomycin, and Tetracycline Are Neutralized

Abstract: It is generally assumed that antibiotic residues in soils select for antibiotic-resistant bacteria. This assumption was tested by separately adding 10 different antibiotics (>200 ppm) to three soil-water slurries (silt-loam, sand-loam, and sand; 20% soil [wt/vol]) and incubating mixtures for 24 h at room temperature. The antibiotic activity of the resultant supernatant was assessed by culturing a sensitive Escherichia coli strain in the filter-sterilized supernatant augmented with Luria-Bertani broth. We found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
66
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 35 publications
(42 reference statements)
2
66
0
Order By: Relevance
“…Previous studies also reported that some soil-adsorbed antibiotics such as tetracycline, tylosin, oxytetracycline and ofloxacin retained antibacterial activity (Chander et al, 2005;Goetsch et al, 2012;Peng et al, 2014). But Subbiah et al (2011) found that β-lactams and florfenicol antibiotics remain bioactive in soils while ciprofloxacin, neomycin, and tetracycline are neutralized. This indicates that residual antibiotics in soil do not necessarily exert a selective pressure, and the degree to which antibiotic remains bioactive depends on the physiochemical properties and biological potency of this chemical.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies also reported that some soil-adsorbed antibiotics such as tetracycline, tylosin, oxytetracycline and ofloxacin retained antibacterial activity (Chander et al, 2005;Goetsch et al, 2012;Peng et al, 2014). But Subbiah et al (2011) found that β-lactams and florfenicol antibiotics remain bioactive in soils while ciprofloxacin, neomycin, and tetracycline are neutralized. This indicates that residual antibiotics in soil do not necessarily exert a selective pressure, and the degree to which antibiotic remains bioactive depends on the physiochemical properties and biological potency of this chemical.…”
Section: Discussionmentioning
confidence: 99%
“…However, knowledge about the relationship between antibiotic sorption behavior and antibacterial activity in soil environments is still scarce (Chander et al, 2005;Goetsch et al, 2012;Halling-Sørensen et al, 2003;Subbiah et al, 2011). Furthermore, although soil adsorbed antibiotics are expected to have the potential to exert biological effects against soil microorganisms, this aspect has not been well-elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, "Candidatus Nitrososphaera viennensis," isolated from neutral soil and demonstrating optimal growth at pH ϳ7.5, required 500 M ATU to stop the majority of nitrification (34). Second, although we have had success in measuring the relative contributions of AOA and AOB to NP in soil slurries by using the RNP assay with or without antibiotics (19), there are several challenges with extending this method into whole soil, including (i) difficulty in distributing aqueous solutions of antibiotics uniformly throughout an unsaturated soil, (ii) antibiotic effectiveness being negated by binding to soil particles (35,36), (iii) variable antibiotic resistance among AOB (this study), and (iv) incomplete removal of acetylene by degassing.…”
Section: Discussionmentioning
confidence: 99%
“…To determine the prevalence of antibiotic resistance, E. coli isolates were tested against a panel of 11 antibiotics that belonged to seven different classes (β-lactams, cephalosporins, amphenicols, tetracyclines, sulfonamides, aminoglycosides and fluoroquinolones) by using a breakpoint assay (Subbiah et al, 2011). Briefly, MAC agar plates (150 mm, diameter) were prepared with each antibiotic at a fixed concentration (given below) that was guided by the Clinical Laboratory Standard Institute (CLSI) recommended minimum inhibitory concentration for E. coli (NCCLS, 2007).…”
Section: Determination Of the Antibiotic Resistance Profilementioning
confidence: 99%